2021
DOI: 10.3389/fpsyt.2021.609458
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity of Nucleus Accumbens and Medial Prefrontal Cortex With Other Brain Regions During Early-Abstinence Is Associated With Alcohol Dependence and Relapse: A Resting-Functional Magnetic Resonance Imaging Study

Abstract: Background: Alcohol dependence (AD) is a chronic recurrent brain disease that causes a heavy disease burden worldwide, partly due to high relapse rates after detoxification. Verified biomarkers are not available for AD and its relapse, although the nucleus accumbens (NAc) and medial prefrontal cortex (mPFC) may play important roles in the mechanism of addiction. This study investigated AD- and relapse-associated functional connectivity (FC) of the NAc and mPFC with other brain regions during early abstinence.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…This is partially in line with Our present findings revealed that future studies using MB factor 4 with no in-plane acceleration would help build upon existing psychiatric research aiming to identify biomarkers targeting specific cortical structures. Atypical FC of the AI has previously been associated with autism spectrum disorders (Ebisch et al, 2011), while impaired FC of the medial prefrontal cortex has been proposed as a potential biomarker for alcohol dependence (Yang et al, 2021). In contrast, commonly used conventional single band sequences may be preferable for studies focusing on the FC of the nucleus accumbens, which has formerly been examined in the context of anorexia nervosa (Haynos et al, 2019) and major depressive disorder (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is partially in line with Our present findings revealed that future studies using MB factor 4 with no in-plane acceleration would help build upon existing psychiatric research aiming to identify biomarkers targeting specific cortical structures. Atypical FC of the AI has previously been associated with autism spectrum disorders (Ebisch et al, 2011), while impaired FC of the medial prefrontal cortex has been proposed as a potential biomarker for alcohol dependence (Yang et al, 2021). In contrast, commonly used conventional single band sequences may be preferable for studies focusing on the FC of the nucleus accumbens, which has formerly been examined in the context of anorexia nervosa (Haynos et al, 2019) and major depressive disorder (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For all three analyses described below, we specifically focused on three rs‐fMRI metrics which have previously been used to gain a better understanding of psychiatric disorders: ALFF, seed‐to‐voxel and ROI‐to‐ROI measures (Ebisch et al, 2011 , Lei et al, 2017 ; Yang et al, 2021 , Zhang et al, 2021 ). All fMRI analyses were carried out using MR images after denoizing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive craving and motivation to drink, along with challenges in moderating consumption are key symptoms associated with AUDs. Clinical studies have consistently associated the prefrontal cortex (PFC) function with these behaviors and symptoms (Grusser et al, 2004 ; Koob, 2014 ; Courtney et al, 2016 ; Blaine et al, 2020 ; Yang et al, 2021 ). In addition, population-level analyses have linked the PFC structure and function with heavy drinking and/or AUD diagnosis (Medina et al, 2008 ; Sorg et al, 2012 ; Wang et al, 2016 ).…”
Section: Prefrontal Cortex Inhibitory Neurons As Specific and Selecti...mentioning
confidence: 99%